Cognitive and functional status of elderly people of a long stay institution of the municipality Divinópolis, Minas Gerais State, Brazil - 10.4025/actascihealthsci.v34ispec.11938 (Acta Scientiarum. Health Sciences, 2012)
This study aimed to evaluate and characterize the functional capacity and cognitive status of elderly people living in a long-stay institution of the municipality of Divinópolis, Minas Gerais State.     The population consisted of 67 elderly people aged between 62 and 102 years, 76% female and 24% male. Data were gathered using the Barthel index of the Mini-Mental State Examination (MMSE) and a form for the social characterization. A significant correlation was observed between the Barthel index and the MMSE, i.e. between functional capacity and cognitive status. Also a significant correlation was detected between education and mental state and between age and mental and functional state. The sex of the participants had no influence on the results. A percentage of 55% had no cognitive impairment, 39% were considered independent and 37% semi-dependent, and only 24% were totally dependent to perform activities of daily living. Therefore, it is emphasized the importance of thinking about the reasons that take to the institutionalization of elderly people.